POTENSI GO-FUN (GOLD AND FUCOIDAN (SARGASSUM SP.) NANOPARTICLE) DALAM DIAGNOSTIK DAN TERAPI RETINOBLASTOMA - Sri Rezki Wahdania J; Indrasari Indrasari (Journal Medical Universitas muhammadiyah Makassar, 2018)
Retinoblastoma is one of the malignant diseases of the eye originating from embryonal tissue. This disease most often occurs in children aged less than 5 years. The prevalence of retionoblastoma ranges from 2-4% of all pediatric malignancies with an incidence of 1 from 15,000-20,000 birth rates. This disease can occur unilaterally or bilaterally. The most common initial symptom is leukoria. The diagnosis of retinoblastoma are biopsy, X photos, ultrasound, Ct-Scan and MRI. However, this detection methods has side effects in children, so a diagnostic method is needed that has minimal side effects. As for the treatment of retinoblastoma are chemotherapy, surgery, focal therapy (cryotherapy, laser thermotherapy), external radiation and enucleation. However, this methods of therapy has side effects in the form of orbital bone growth disorders and mortality due to secondary malignancy. The use of chemotherapy not only attacks cancer cells but also can attack healthy cells so that patients can experience disorders such as diarrhea, anemia, etc. So from tha , the right and effective method of detection and therapy is needed. The writing of this review is to examine the most effective and efficient detection and therapy methods for treating retinoblastoma. In this review, there were Pubmed and Google Scholar-based data searches and no factor index restrictions using the keywords Gold Nanoparticle, fucoidan, nanoparticle, retinoblastoma and Surgassum sp. A review showed that Gold Nanoparticle (GNP) effectively used in the detection of retinoblastoma and Fucoidan nanoparticle is effective for the treatment of retinoblastoma. Gold Nanoparticle (GNP) and Fucoidan nanoparticle are potentially diagnostic and therapy on retinoblastoma .